2015
DOI: 10.1039/c5cy00327j
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of ethanol over hydroxyapatite-based Ca-enriched catalysts with various carbonate contents

Abstract: The Guerbet reaction of ethanol to produce heavier products was performed over a series of extensively characterized carbonate-containing hydroxyapatites (HAPs) with different Ca/P ratios and thus different densities, strengths and natures of acid and basic sites. These properties were correlated with the reactivity of the solids and an optimal ratio between the amount of acid and basic sites was evidenced (ca. 5). The best performance was accordingly obtained over the Hap-CO 3 catalyst, which gave a yield of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
68
1
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 27 publications
7
68
1
5
Order By: Relevance
“…Nevertheless, it should be kept in mind that these compounds also contain A‐type carbonates, even in larger amount. Furthermore, opposite to what was recently reported for other over‐stoichiometric compounds[10e], that were prepared in very different conditions and therefore involved a large excess of calcium (Ca/P ratios introduced in solutions ranging from 2 to 6.6), no segregation of any calcium phase could be detected. Moreover, as already described elsewhere, from CO adsorption and XPS data,[35b], Ca 2+ ions are only slightly exposed at the surface, being rather relaxed in sub‐surface location.…”
Section: Resultscontrasting
confidence: 90%
See 1 more Smart Citation
“…Nevertheless, it should be kept in mind that these compounds also contain A‐type carbonates, even in larger amount. Furthermore, opposite to what was recently reported for other over‐stoichiometric compounds[10e], that were prepared in very different conditions and therefore involved a large excess of calcium (Ca/P ratios introduced in solutions ranging from 2 to 6.6), no segregation of any calcium phase could be detected. Moreover, as already described elsewhere, from CO adsorption and XPS data,[35b], Ca 2+ ions are only slightly exposed at the surface, being rather relaxed in sub‐surface location.…”
Section: Resultscontrasting
confidence: 90%
“…As far as OH vacancies are concerned, they might also directly contribute to the loss of basicity because of their possible involvement as Lewis acidic sites as proposed by Silvester et al Note however that from Table , the OH vacancies concentration ([⬜ OH ] ∝ x +A+B) is not strictly associated with the loss of OH (due to substitution on the same site of A‐type carbonate) ([OH] ∝ 2– x –2A–B). Thus, contrary to the [OH] concentration, the concentration of OH vacancies is similarly impacted by A‐ or B‐type carbonatation.…”
Section: Resultsmentioning
confidence: 96%
“…As compared to MgO, a greater fraction of the acetaldehyde formed undergoes aldol condensation on HAP. Silvester et al 194 synthesized modified hydroxyapatites and found an optimal n-butanol yield on materials with an acidity/basicity ratio of 5. Fine-tuning of both the nature and the amount of acidbase sites is a key to optimize both conversion and selectivity of the Guerbet reaction.…”
mentioning
confidence: 99%
“…The importance of acid-base bifunctionality has once more been confirmed in two recent papers. 193,194 Hanspal et al 193 compared HAP and MgO for ethanol condensation using isotopic transient kinetic analysis together with acidbase characterization. HAP was found to expose a higher density of both basic and weak acidic sites which explained why it was about three times more active.…”
mentioning
confidence: 99%
“…The Ca/P ratio is strongly linked with different densities, strengths and natures of acid and basic sites. Selectivity towards Guerbet alcohols was found to increase rather linearly with the number of acidic sites up to 658 μmol g −1 for a carbonated HAP with Ca/P ratio of 1.70 (Table , entry 10), whereas no correlation with the number of basic sites was found . However a sharp increase in selectivity was found by plotting it versus the acidity to basicity ratio, R AB , with a maximum at 4.8 for the carbonated apatite.…”
Section: Guerbet Condensation Reactionsmentioning
confidence: 99%